Multivalent cation and polycation polymer preparations influence pharmacokinetics of dolutegravir via chelation-type drug interactions. (April 2021) - Enoki, Yuki; Kishi, Nagomi; Sakamoto, Kazuki; Uchiyama, Eri; Hayashi, Yukitaka; Suzuki, Norihiro; Ito, Motoyasu; Taguchi, Kazuaki; Yokoyama, Yuta; Kizu, Junko; Matsumoto, Kazuaki
Abstract: Dolutegravir (DTG) is an integrase inhibitor, whose gastrointestinal absorption is impaired by the formation of chelates with multivalent metal cation preparations. However, little is known regarding the interactions of DTG with preparations containing other multivalent metal cations or with polycation polymer preparations. This study examined how the pharmacokinetics of DTG are affected by co-administration with Al(OH)3, LaCO3, and the polycation polymers bixalomer (Bxl) and sevelamer (Svl). Prior to oral administration of DTG (5 mg/kg), rats were orally administered Al(OH)3 (150 or 300 mg/kg), LaCO3 (50 or 75 mg/kg), Bxl (250 or 500 mg/kg), or Svl (300 or 600 mg/kg). Serum concentrations of DTG were then measured over the next 24 h. Compared to the administration of DTG alone, its co-administration with Al(OH)3, LaCO3, Bxl, and Svl led to reduced serum concentration of DTG, and consequently, a significantly reduced area under the curve. These comparisons also revealed a considerable reduction in the maximum concentration, suggesting that the interactions of these agents with DTG in the intestinal tract inhibit absorption of DTG. The above results demonstrate that Al(OH)3, LaCO3, Bxl, and Svl affect the pharmacokinetics of DTG and indicate the need for caution when combining any of the above preparations with DTG. Graphical abstract: Image 1